2018
DOI: 10.17576/jem-2018-5201-23
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Muslim Household Basic Needs Consumption Expenditures

Abstract: This paper focuses on current household expenditure in an environment characterised by a high cost of living and modernisation. In order to cope with the current economic situation, individual vary in their consumption levels and lifestyles. In this study, basic needs expenditure refers to four main groups of household expenditure, namely food, housing, transportation and communication given that they make up a significant part of total household expenditure. Furthermore, the different budget constraints that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Moreover, Kulub Abd. Rashid et al [19] asserted that low financial literacy levels will have an impact on financial well-being and socioeconomic status. Meanwhile, a study conducted by Krishnakumare and Singh [20] in the Tamil Nadu district of India found that factors such as financial well-being and the lack of financial literacy among poor households in family institutions have resulted in serious financial stress, which caused them to be financially unwell and affected the SES of this group.…”
Section: The Role Of Financial Well-being (Fwb)mentioning
confidence: 99%
“…Moreover, Kulub Abd. Rashid et al [19] asserted that low financial literacy levels will have an impact on financial well-being and socioeconomic status. Meanwhile, a study conducted by Krishnakumare and Singh [20] in the Tamil Nadu district of India found that factors such as financial well-being and the lack of financial literacy among poor households in family institutions have resulted in serious financial stress, which caused them to be financially unwell and affected the SES of this group.…”
Section: The Role Of Financial Well-being (Fwb)mentioning
confidence: 99%
“…Food Expenditure Food expenditure is any form of financial transaction to buy food and non-alcoholic beverages used at home (United Nations, 2000; Ishida et al, 2003;Tey et al, 2008;Latimaha, 2017;Mien & Said, 2018;Rashid et al, 2018;Manajit et al, 2020). Household income is one of the most important factors significantly related to food expenditure.…”
Section: 4mentioning
confidence: 99%
“…Income is one factor that impacts housing expenses (Manajit et al, 2020;Wahab et al, 2018;Rashid et al, 2018;Mien & Said, 2018;Eichholtz & Lindenthal, 2014). However, the influence of income on housing expenditure is not well established.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations